A Systematic Literature Review of Electricity Load Forecasting using Long Short-Term Memory - Salleh N.S.M.; Suliman A.; Jrgensen B.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Brain; Deregulation; Electric load forecasting; Electric power plant loads; Electric utilities; Learning algorithms; Statistical tests; Electricity load; Electricity load forecasting; Evaluation metrics; Load predictions; Long term planning; LSTM; Machine learning algorithms; Medium-term planning; Review papers; Systematic literature review; Long short-term memory